Was Electricity a General Purpose Technology? Evidence from Historical Patent Citations - Moser, Petra; Nicholas, Tom (American Economic Review, 2004)
Was Electricity a General Purpose Technology? Evidence from Historical Patent Citations by Petra Moser and Tom Nicholas. Published in volume 94, issue 2, pages 388-394 of American Economic Review, May 2004